Investigating Symptomatic Vitreous Opacities: An Online Survey and Field of View Reconstruction - Lippek, Jaryi; Rynko, Leonie; Framme, Carsten; Kermani, Omid; Johannsmeier, Sonja; Ripken, Tammo (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Symptomatic vitreous opacities (SVO) are a condition that can significantly affect patientsʼ quality of life. This online survey aims to contribute to the scientific understanding of symptomatic vitreous opacities, by investigating the subjective burden and individual perception of floaters, using a novel tool for field of view reconstruction. In addition, correlations with demographic data and refractive status will be analysed to identify patterns and potential influencing factors.Methods We introduce a VO-related online survey covering patient education, experience with floaters and treatment, refraction error and eye diseases, quality of life, and a new sketching tool to simulate the individual field of view with VO. The data were collected between August 2022 and November 2023 and are analysed for correlations; participantsʼ answers are compared to the sketching tool results. We used linear regression with gradient descent to test whether a subjective suffering index from the questionnaire can be matched with an objective suffering index from the new sketching tool.Results A total of 1502 people participated in the survey, of whom, 1384 reconstructed their field of view by positioning a total of 10,571 VO. There was no robust correlation between the sketched floaters and the subjective degree of suffering. Translucent VO types are more frequent in younger attendees. The dataset shows a higher prevalence of myopic participants and a lower prevalence of hyperopes with VO compared to global data.Conclusion We were able to collect the largest dataset to date quantifying individual experience with floaters. As evidenced by the large number of participants with SVO and individual remarks on their psychological burden, greater effort is needed to improve the care for floater patients.
Keywords: vitreous opacities; vitreous floaters; survey; myopia; field of view; quality of life